Experiencing the Tangible Past through Virtual Reconstruction: Cultural Heritage of Buildings and their Environmental Boundaries - Mojtaba Navvab (mediaGEO soc. coop., 2019)
These paper present accurate reconstructions and virtual representations of buildings of cultural heritage, which have been developed techniques of visualization and auralization in virtual environment. Computer graphics allows to reconstruct and experience the visual and acoustic conditions of the past with a high degree of realism and to deepen the knowledge of cultural heritage.